Risk factors of doxorubicin-induced cardiomyopathy in non-muscle- invasive bladder cancer - Sabudi, I Made Nugraha Gunamanta; Hendri, Ahmad Zulfan (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundDoxorubicin is an anthracycline antibiotic widely used as a chemotherapeutic agent to treat solid tumors and hematologic malignancies. Bladder cancer is the second most common genitourinary malignancy and can be classified into muscle-invasive bladder cancer and non-muscle-invasive bladder cancer (NMIBC). In Indonesia, NMIBC is treated by doxorubicin instillation. Several risk factors have been suggested to be associated with doxorubicin-induced cardiomyopathy, but on their quantitative effects no consensus has as yet been reached. This study aimed to determine the risk factors of doxorubicin-induced cardiomyopathy in NMIBC patients with intravesical doxorubicin instillation. MethodsA cross-sectional study was conducted involving 74 NMIBC patients who received local treatment by doxorubicin instillation after transurethral resection of bladder tumor (TURBT). Data were collected on the risk factors that may be favorable to doxorubicin-induced cardiomyopathy, namely age, sex, hypertension, type 2 diabetes mellitus, smoking, and NMIBC risk classification. The dependent variable was cardiomyopathy with decreasing left ventricular ejection fraction (LVEF) below 50 %. Multiple logistic regression was used to analyze the data. ResultsThe prevalence of cardiomyopathy was 6.75% (5/74). Type 2 diabetes mellitus was a significant risk factor for doxorubicin-induced cardiomyopathy among our subjects (aOR=34.30;95% C.I.:1.36-865-86;p=0.032). In contrast, age, sex, risk classification, hypertension, and smoking were nonsignificant predictors for doxorubicin-induced cardiomyopathy (p>0.05). ConclusionThis study demonstrated that type 2 diabetes mellitus increased the risk of cardiomyopathy in doxorubicin users among patients with NMIBC. More research is necessary regarding the mechanisms underlying type 2 diabetes mellitus as a risk factor for doxorubicin-induced cardiomyopathy.